Effect of dietary lysine and genetics on growth and indices of lysine catabolism in rainbow trout (Oncorhynchus mykiss). (11th July 2016) - Gatrell, S.K.; Silverstein, J.T.; Barrows, F.T.; Grimmett, J.G.; Cleveland, B.M.; Blemings, K.P.
Abstract: The level of the essential amino acid lysine is of concern in trout feed. The objective of this study was to investigate the response of different families of fish to lysine‐deficient (LD) versus lysine‐adequate (LA) soy protein‐containing diets. For each treatment combination, there were five replicates. As expected, feed efficiency ( p  <   .0001) and thermal growth coefficient (TGC, p  <   .0001) were improved in fish fed the LA compared to the LD diet. Hepatosomatic index (HSI, p  <   .01) and whole‐body lipid content ( p  <   .01) were higher for fish consuming the LD compared to the LA diet. There was no effect ( p  >   .05) of diet on hepatic lysine α‐ketoglutarate reductase (LKR) activity, LKR mRNA abundance or lysine oxidation. There was a family effect on feed efficiency ( p  <   .0001), TGC ( p  <   .0001) and condition factor ( p  <   .05) and there was a trend for differences in oxygen consumption ( p  <   .07) across families while consuming the LD diet; however, there was no effect on ammonia excretion, HSI, lipid content, efficiency of nitrogen or lysine retention or indices of lysine catabolism. One family, in particular, had more favourable feed efficiency and thermal growth coefficient when fed the LD diet, indicating that it may possess an enhanced genetic potential for performance when consuming LD, soybean meal‐containing diets.